Managing strategic change at the regional level: Regional networks of economic development and industry clusters - Cristina Martinez (European Regional Science Association (ERSA), 1998)
Regional Development Networks of private and public organisations is a contemporary phenomenon that is reshaping strategies of local development by introducing new agents and more dynamism and flexibility in the decision making process. This approach reflects new trends in corporate and business development, balancing the tensions produced by competition and collaboration. Regions as networks incubators are regions with specific characteristics enhancing an emergent and evolving movement of networking between organisations working for the regional development. The purpose of this paper is to present the network scenario of two regions from Spain and Australia that exemplify the emergence and evolution of networks' incubator and the relevance to their regional development. Both regions are facing economic restructuring as a result of regional spatial competition on the global market. These regions could be characterised as learning regions and a definition of the network incubator will be provided. The paper will argue that regional networks are a development tool, which could act as a catalyst in stimulating economic revitalisation. It is possible to engineer this tool, stimulating the conditions of the region as a network incubator. Key Words: regions of networks' incubators, learning regions, local development
Keywords: 330